1991
DOI: 10.2307/1941758
|View full text |Cite
|
Sign up to set email alerts
|

Tropical Soil Fertility Changes Under Monocultures and Successional Communities of Different Structure

Abstract: For 5 yr we monitored the fertility of a volcanic-ash derived Inceptisol at a site in the humid tropics of Costa Rica. After forest felling and burning, we established four treatments in a randomized block design with six blocks: a sequence of monocultures (two crops of maize [Zea mays] followed by cassava [Manihot esculenta], then the tree species Cordia alliodora), successional vegetation, a mimic of successional vegetation that was physiognomically similar to the model but shared no species with it, and a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
96
0
7

Year Published

1994
1994
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(107 citation statements)
references
References 39 publications
4
96
0
7
Order By: Relevance
“…Kirby and Potvin (2007) did not find any linear relationship at soil profiles under forests in Eastern Panama either. The environmental factors of different region (Ewel et al 1991;Berendse 1998;Forrester et al 2006) and various forest productivities (Vandermeer 1989;Tilman et al 1997) may cause the different relationships. And more studies are needed to explain the correlation between biodiversity and SOC in order to develop forest management and establish forest with great C sequestration.…”
Section: Discussionmentioning
confidence: 99%
“…Kirby and Potvin (2007) did not find any linear relationship at soil profiles under forests in Eastern Panama either. The environmental factors of different region (Ewel et al 1991;Berendse 1998;Forrester et al 2006) and various forest productivities (Vandermeer 1989;Tilman et al 1997) may cause the different relationships. And more studies are needed to explain the correlation between biodiversity and SOC in order to develop forest management and establish forest with great C sequestration.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the nutrient recycling characteristics of a species are an important selection criteria when evaluating suitability to particular environmental conditions. Ewel et al (1991) found that similar soil-nutrient dynamics can be achieved by both successional vegetation and human-built mimics of that vegetation. Based on the differences of nutrient resources use and returns, we can create structures to establish and maintain nutrient pools within human-designed ecosystems, or human-directed successional situations.…”
Section: Mg Hamentioning
confidence: 92%
“…However, increasing the diversity of green roof plants may help to increase a roof's value as habitat for other species. Research has also demonstrated that diversity increases productivity of an ecosystem (Tilman 1997), increases stability of that ecosystem (Tilman and Downing 1994), and increases retention of soil nutrients (Ewel et al 1991). This paper will evaluate the potential for extensive green roofs to provide increased ecological function in urban areas as compared to impervious surface rooftops by discussing two green roof case studies from the Southeastern and Northeastern United States as well as previously published data.…”
Section: Introductionmentioning
confidence: 99%